Effect of oral mexiletine on the cough response to capsaicin and tartaric acid. Issue 2 (1st February 2000) - Fujimura, Masaki; Kamio, Yumie; Myou, Shigeharu; Hashimoto, Takuma
Abstract : BACKGROUND: The effect of the orally active local anaesthetic mexiletine on the cough response to two different tussive agents, a C-fibre ending stimulator capsaicin and a chemostimulant tartaric acid, was examined in normal subjects. METHODS: The cough threshold, defined as the lowest concentration of capsaicin (C5 -CP) or tartaric acid (C5 -TA) causing five or more coughs, and histamine induced bronchoconstriction were measured three hours after a single oral dose of 300 mg mexiletine or placebo in 14 normal subjects. RESULTS: Mexiletene in a mean (SE) serum concentration of 0.99 (0.04) μg/ml significantly increased C5 -TA from a geometric mean (SE) of 32.0 (1.27) mg/ml with placebo to 49.9 (1.34) mg/ml, but C5 -CP did not differ significantly between treatment with mexiletine (12.2 (1.33) μM) and placebo (14.9 (1.23) μM). CONCLUSIONS: These results suggest that the cough response to capsaicin and tartaric acid may be mediated in part via different neural pathways.